Resistance to barley yellow dwarf virus, powdery mildew and leaf rust in wheat x Thinopyrum backcrosses - Sharma, Hari; Ohm, Herbert; Shaner, Gregory (Phytoprotection, 2004)
AbstractWheat (Triticumaestivum) relatives are sources of useful genes for disease resistance. Chromosomally segregating populations of intergeneric hybrids between wheat and its distantly related species provide opportunity to study and introgress multiple disease resistance. While introgressing resistance to barley yellow dwarf virus (BYDV) from Thinopyrum into wheat, which is susceptible to BYDV, we scored powdery mildew (Erysiphaegraminis) and leaf rust (Pucciniatriticina) resistance, and chromosome numbers in second and third backcrosses (BC2 and BC3) of intergeneric hybrids of wheat with Thinopyrum ponticum and Thinopyrumintermedium. The frequency of multiple resistance to all the three diseases was low or became low when selection was applied for BYDV resistance and low chromosome numbers. Selection for fewer alien chromosomes while maintaining BYDV resistance was more effective in wheat x T. intermedium than in the wheat x T. ponticum cross. Mean chromosome numbers were significantly different in BC3 generation between BYDV resistant and susceptible plants in both crosses. Significant negative correlations between chromosome numbers and enzyme-linked immunosorbent assay (ELISA) values showed that as the critical Thinopyrum chromosome(s) were eliminated, susceptibility to BYDV increased. Results indicated that it is unlikely that genes for full resistance to all three diseases can be transferred simultaneously from Thinopyrum to wheat.